Restriction endonucleases HindII and TaqI cleave DNA with mismatched nucleotides within their recognition sequences. - Jiricny, J (1986)
Restriction endonucleases HindII and TaqI, but not SalI, were found to efficiently cleave synthetic hexadecanucleotide duplexes which contained either an A/C or a G/T mismatch within their respective restriction sites. Double-stranded M13 DNAs with identical mismatches were also cleaved under the assay conditions. These results suggest that the distortion of the DNA duplex, caused by these purine/pyrimidine mismatches is not sufficiently large so as to interfere with the recognition and the subsequent cleavage of the DNA by these two enzymes. HindII and SalI, but not TaqI, were furthermore shown to hydrolyze the two strands of the duplex with different rates. The differences between the mode of recognition of their respective restriction sites by these three enzymes are discussed.